Repetitive negative thinking and emotion regulation as mediators of the association between activity-related behaviours and depression - Stephanie Lu; Joanne A. McVeigh; Rodrigo Becerra; Romola S. Bucks; Michael Hunter; Kristin Naragon-Gainey (Journal of Affective Disorders Reports, 2024)
Background: More physical activity and less sitting time are associated with less severe depression, but the psychological mechanisms underlying these associations remain unclear. Repetitive negative thinking (RNT) and difficulties regulating emotions are key transdiagnostic risk factors for depression and are key targets in current psychotherapies. The current study tested RNT and emotion regulation difficulties as mediators of the associations of depression with (1) physical activity and (2) sitting time. Method: We analysed data from community-dwelling adults in middle to late adulthood (aged 46–68 at baseline; N = 1189) from The Busselton Healthy Ageing Study, assessed three times across 11 years. Serial mediation models were tested cross-sectionally, prospectively, and persistently (i.e., throughout the course of the study). Results: Results indicated support for cross-sectional serial mediation for physical activity and sitting time models, but not for longitudinal models. However, RNT individually mediated the persistent sitting time-depression model. Limitations: All data was self-reported. Mediators could only be assessed at the last time point within the larger study, constraining the temporal associations that could be tested. Further studies assessing mediators across time using different methods and time intervals are needed. Conclusions: Our findings provide some initial evidence for psychological pathways by which the benefits of greater physical activity and lower sitting time may be conferred. If supported longitudinally and in experimental designs, increased physical activity and reduced sitting time may be beneficial therapeutic targets for older adults at risk for depression and/or who experience difficulties with rumination and emotion regulation.